Student diversity and student voice conceptualisations in five European countries: Implications for including all students in schools. (March 2022) - Messiou, Kyriaki; Bui, Lien Thien; Ainscow, Mel; Gasteiger-Klicpera, Barbara; Bešić, Edvina; Paleczek, Lisa; Hedegaard-Sørensen, Lotte; Ulvseth, Hilde; Vitorino, Teresa; Santos, Jorge; Simon, Cecilia; Sandoval, Marta; et al.
This article analyses the ways in which notions of student diversity and student voice are defined in five European countries, two terms directly related to notions of inclusion. In so doing, it examines links between the two terms, noting that, often, they are used in international research without acknowledging the ways that they are defined within particular national contexts. Using literature and policy documents from five countries (i.e. Austria, Denmark, England, Portugal and Spain), the article highlights similarities as well as differences in the various contexts. Through the analysis of these texts, the paper concludes that diversity is conceptualised in five ways, although there is occasionally overlap of different conceptualisations in some of the countries. Meanwhile, the term 'student voice' is a term that is not used in some of the countries' policies. Instead, other terms that relate to student voice, such as 'participation', are used. The paper discusses the implications of these varied understandings for the promotion of the inclusion of all students in schools.